Customer Adoption of Neobank Services from a Technology Acceptance Perspective – Evidence from Hungary - Nagy, Szabolcs; Molnár, László; Papp, Adrienn (Decision Making: Applications in Management and Engineering, 2024)
The rapid technological development of recent years has led to a transformation and digitalisation of financial services, resulting in an increasing number of neobanks. At the same time, consumer acceptance of the services offered by these branchless banks is a key success factor for their widespread adoption. The aim of our research is to understand the individual decision-making process of potential and current neobank users. This paper seeks to explore the relationships between the factors that influence customers’ intention to use neobank services by extending the widely used technology acceptance model (TAM) to include trust. To answer the research questions, we conducted an online questionnaire survey in Hungary in 2022. Using structural equation modelling (SEM) on a sample of 475 respondents, we found that intention to use is directly influenced by attitude towards use, which in turn is positively influenced by trust, perceived usefulness and perceived ease of use. Based on these results, we recommend that neobanks should focus on building positive attitudes towards their services by emphasising trust, reliability, ease of use and usefulness of their services.